Strain concentration of double-edge hole ductile composites in the full range of deformation by digital image correlation - Sanjay Kumar; Chang-Mou Wu; Po-Chun Lin; Jieng-Chiang Chen; Yoshinobu Shimamura (eXPRESS Polymer Letters)
This study investigated variations in strain concentration factors (Kɛ) within the full deformation range of self-reinforced poly(ethylene terephthalate) composites (srPETs) with double-edge semicircular holes (DESH) using digital image correlation (DIC) at different width-to-diameter (W/D) ratios. The value of Kɛ agrees with the theoretical concentration factor (Kt) within the elastic deformation range; then, it increases rapidly to a peak because of plastic deformation. Therefore, the change in Kɛ was divided into different stages based on the spread of the yield extent (beginning from the hole edge). These results will help improve the understanding of the yielding phenomenon of open-hole materials and provide early warnings before final material damage. Kɛ decreased in both the elastic and plastic regions with a decrease in W/D; however, there was an exception when the W/D ratio = 1.5. Therefore, the geometric configuration W/D > 1.5 was recommended for designing secure structural ductile composites. The Kɛ of DESH is lower than that of circular holes (CH) in both the elastic and plastic regions for the hole effect. Thus, composites with DESH should be preferred as an alternative for structural applications.